PRINCIPLES OF MALAYSIAN LAND LAW - Ainul Jaria Maidin; Azlinar Sufian; Fauziah Amd Noor; Nor Asiah Mohamad; Sharifah Zubaidah Syed Abdul Kader (Kuala Lumpur : LexisNexis Malaysia Sdn Bhd, 2022)
This book seeks to set out the concepts and principles of Malaysian Land Law that is simplified to enable readers, especially Law students, to grasp a clear understanding of the subject. It is useful for those interested to know more about the modified Torrens System implemented in the Malaysian land administration system. The book focuses on explaining the statutory provisions of the major areas of Land law supported with case law wherever relevant and necessary. The writing style and distinctive way of presentation that is interactive with the readers addresses common areas of confusion. Topics are broken down into sections that are easy to navigate and understand. Balancing brevity with detail and rigour with accessibility, this book is a truly modern textbook that supports and motivates its readers, helping them to understand and enjoy learning Land Law which is otherwise a complex subject.
1. Introduction -- 2. General Concepts of Land Ownership -- 3. Rights and Powers of the State Authority -- 4. Dealings and Registration of Dealings -- 5. Indefeasibility of Titles and Interests -- 6. Transfers -- 7. Easement -- 8. Leases and Tenancies -- 9. Security Dealings -- 10. Restraint on Dealings -- 11. Management of Reserved Land -- 12. Compulsory Acquisition of Land -- 13. Strata Titles Law in Malaysia -- 14. Principles of Islamic Land Ownership
Includes index
LULUS
Keywords: Land Law -- Malaysia